Virtual Education in the Formative Process of Leveling Students at Chemical Sciences, Central University of Ecuador Images through Artificial Intelligence - Yépez Padilla, Myrian Mishell; Espinel Armas, Elithsine E.; Brito-Dumancela, Carlos Alberto; Mora-Gilces, Tatiana Stephanie; Naranjo Lopez, Cristina Monserrat (Revista Ecos de la Academia, 2024)
A catch-up course it’s an academic program before starting a career. It was implemented in Ecuador back in 2012. The purpose of the course is to improve the quality of education and to decrease the drop off rate in schools. However, the COVID19 pandemic had a big impact on the course, forcing it to keep it as a virtual course. We got interested in describing the development of the training process in the students of the leveling course from December 22 to March 23. The population consisted of 326 students from the Chemistry, Biochemistry and Pharmacy colleges. 253 answered the questionnaire, which was previously validated by a group of experts who determined the test was statistical reliable at 0.92. The results were processed through R Core Team 2023 software by a multiple correspondence analysis. We concluded that the teaching staff has responded well to the challenges of virtual teaching. They have adopted effective strategies to warrant the teaching and learning process. However, the virtual modality represents an even greater challenge for students. They face new barriers such as connectivity problems and communication difficulties, perceiving the virtual modality as an educational experience that is not very satisfactory.